Effect of metal type on basic soap pyrolysis produce bio-gasoline. Issue 1 (April 2020) - Puspawiningtiyas, E; Pratiwi, M; Neonufa, G F; Purwadi, R; Isyami, A N; Elizabeth, L; Soerawidjaja, T H; Subagjo,; Prakoso, T
Abstract: The basic metal soap from oleic acid submitted to pyrolysis to produce gasoline-like hydrocarbon fuels (biogasoline). The pyrolysis was carried out in a semi-batch reactor at 450°C and a feeding rate of 5 g/15 min. The influences of various metal (Ca, Mg, Zn) hydroxides, which are used to made basic soap, have been examined. The bio hydrocarbon of basic metal soap was characterized by GC-FID and FT-IR, showing the formation of paraffin, iso-paraffin, olefin, ketone, and aromatics. The liquid fraction derived from the pyrolysis of basic metal soap was dominated by gasoline (C7-C11) fraction hydrocarbon. The maximum yield of light C7-C11 hydrocarbon was 82.3 %-mol fraction of basic Ca soap and the highest yield of biohydrocarbon reached 34.77 wt.% from pyrolysis of basic Mg soap.